PROCEDURAL OUTCOMES OF PRIMARY PERCUTANEOUS CORONARY INTERVENTION IN ELDERLY PATIENTS WITH STEMI - Daud, Muhammad Yousuf; Khan, Matiullah; Awan, Muhammad Saleem; Hayat, Umar; Tuyyab, Farhan (Journal of Ayub Medical College Abbottabad, 2018)
Background: Cardiovascular disease (CVD) is the leading cause of death worldwide, and coronary artery disease (CAD) is the most prevalent manifestation associated with high mortality and morbidity. Older age is independent predictor of cardiovascular mortality and death. Elderly may experience high rates of complications following acute STEMI. Optimal reperfusion strategy in elderly following STEMI remains under debate due to their exclusion from trials evaluating various treatment modalities. Primary PCI has emerged as treatment of choice in patients presenting with acute STEMI in a certain window period. The rationale of this study is to help us determine the outcome of primary PCI in the local elderly population. Methods: The study was designed as descriptive cross-sectional study and was carried out at AFIC, NIHD hospital Rawalpindi over a six months period. A total of 105 adults with STEMI were included in study. Data was analysed using SPSS 19.0 version. Results: Total 105 patients were included in the study according to the inclusion criteria of the study. There were 102 (97.1%) patients who successfully achieved TIMI II flow post Primary PCI. Conclusion: We concluded that outcome of primary pci in local elderly population is favourable which leads to a consensus that primary PCI should be offered to every elderly patient presenting to tertiary care hospital with well-equipped Cath lab and experienced staff. Keywords: Primary PCI; elderly; myocardial infarction